2015
DOI: 10.18547/gcb.2015.vol1.iss1.e19
|View full text |Cite
|
Sign up to set email alerts
|

Visual Characterization of Misclassified Class C GPCRs through Manifold-based Machine Learning Methods

Abstract: G-protein-coupled receptors are cell membrane proteins of great interest in biology and pharmacology. Previous analysis of Class C of these receptors has revealed the existence of an upper boundary on the accuracy that can be achieved in the classification of their standard subtypes from the unaligned transformation of their primary sequences. To further investigate this apparent boundary, the focus of the analysis in this paper is placed on receptor sequences that were previously misclassified using supervise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These results were further confirmed from the viewpoint of visualization-oriented fully unsupervised machine learning methods (that is, methods that attempted sequence discrimination into subtypes without knowledge of sequence-to-subtype assignment). Results clearly indicated that the subtypes shown to be worse discriminated by supervised classifiers were also those shown to heavily overlap in unsupervised visualization models from different unaligned sequence data transformations 31 .…”
Section: Datamentioning
confidence: 99%
“…These results were further confirmed from the viewpoint of visualization-oriented fully unsupervised machine learning methods (that is, methods that attempted sequence discrimination into subtypes without knowledge of sequence-to-subtype assignment). Results clearly indicated that the subtypes shown to be worse discriminated by supervised classifiers were also those shown to heavily overlap in unsupervised visualization models from different unaligned sequence data transformations 31 .…”
Section: Datamentioning
confidence: 99%
“…Results clearly indicated that the subtypes shown to be worse discriminated by supervised classifiers were also those shown to heavily overlap in unsupervised visualization models from different unaligned sequence data transformations [6].…”
Section: Previous Research On Gpcr Class C From a Data Curation Persp...mentioning
confidence: 99%
“…[4] misclassification analysis [5,6] Tracking the evolution of class C GPCR chapter 6 [7] database Topological sequence segments discriminate chapter 7 [8,9] betw. class C GPCR subtypes Feature selection for the identification chapter 8 [10,11] of subtype-discriminating n-grams.…”
Section: Topicmentioning
confidence: 99%